E-Waste Management – Problems and Solutions - J. Vijayan (REVIEW OF SOCIAL SCIENCES, 2013)
Electrical and Electronic Equipments (EEE) are inevitable to human beings from cradle to grave. As the population increases at geometric progression and the life span of the EEE slashes drastically due to numerous reasons, the accumulation of Electrical and Electronic Equipment Waste (E-Waste) occurs at an alarming rate ; creating Environmental, Social and economic impact to society. A report of the United Nations predicted that by 2020, e-waste from old computers would jump by 400 per cent on 2007 levels in China and by 500 per cent in India. Additionally, e- waste from discarded mobile phones would be about seven times higher than 2007 levels and, in India, 18 times higher by 2020. This large scale accumulation of the E- Waste should be controlled, harmful element in the E-Waste need be reduced, Best Available Technology need be applied for recycling E-Waste, recycling units in both formal and informal sectors need be integrated by considering Indian condition, Extended Producers Responsibility (EPR) need be effectively implemented and E- Waste Management Laws should be enforced strictly. In this respect, all the stake holders should be made aware of impact of e-waste. If the pollution from the e-waste is not brought within the limit, it shall wipe out human beings from the glob itself. On the other hand, e-waste recycling in India can be made profitable and environment- friendly, if it is managed scientifically through the integration of the informal sector with formal sector.